Kebijakan Pelayanan Izin Mendirikan Bangunan di Dinas Cipta Karya dan Pertambangan Deli Serdang - Efridawati Efridawati; Anggreini Atmei Lubis (Universitas Medan Area, 2015)
This study aims to determine how the policy of the service functions of the Department of Human Settlements and Mining District of Deli Serdang in the granting of building permit (IMB), the obstacles are faced by Dinas Cipta Karya and Mining District of Deli Serdang in the implementation of the Building Permit (IMB) and efforts are made Dinas Cipta Karya and Mining Deli Serdang in order to overcome obstacles to the provision of service standard building permit. The results of research and discussion to explain the implementation of the administration building permit, shall refer to the Regional Regulation No. 6 In 2011 On Licensing Certain. Implementation of the regulation was made in an effort to realize the program of improvement of Deli Serdang regency as the area rapidly developing, which brings together new concepts and old, although until recently, the lack of spatial concepts clearly and unequivocally that resulted in Deli Serdang district has experienced flooding problems and system traffic congestion is getting worse, due to the arrangement of the building has not kept pace with the spatial allocation. Constraints faced in the implementation of the provision of building permit is the low level of public knowledge of the importance and benefits have IMB.